Manhājun Muqtarahun li Ta’līm Al-Lughah Al-‘Arabiyyah lil Mubtadiīn Al-Indunīsiyyîn bi Istikhdmi An-Nadzāir Al-Mukhādi’ah fī (KBBI) min Harfi A ilā Harfi Z Namūdzajan - Dewi Yulisma; Evi Khulwati (Mauriduna: Journal of Islamic Studies, 2021)
المنهج هو عنصر أساسي من العناصر التعليمية لكل مؤسسة تعليمية. وهو عامل من عوامل التعلم والتعليم الذي يحتاج إلى الاهتمام أكثر في تحسين جودة عملية التعلم والتعليم. والمنهج الجيد هو الذي يراعي ويعتمد على حاجة المتعلم ويمكن أن يواصله إلى الأهداف المرجوة. إن منهج الذي اقترحت الباحثة هو منهج تعليم اللغة العربية باستخدام النظائر المخادعة للطلاب المبتدئين الإندونيسيين في معجم اللغة الإندونيسية الكبير (KBBI) من حرف Aإلى Z نموذجا. وبهذا المنهج يمكن للطلاب المبتدئين الإندونيسيين الحصول على السهولة في تعلم اللغة العربية حيث إن الباحثة عرضت النظائر المخادعة ومعانيها في محتوى المنهج. وهدفت الدراسة إلى اقتراح منهج لتعليم اللغة العربية للطلاب المبتدئين الإندونيسيين باستخدام النظائر المخادعة في معجم اللغة الإندونيسية الكبير (KBBI) من حرف A إلى Z نموذجا. Curriculum is an important element of the learning element in every educational institution. It needed to improve the quality of learning and teaching processes. The method used in this research was analytical descriptive method by collecting Homonyms in KBBI Dictionary from letters A to letters Z, then from the vocabulary, the researcher proposes a curriculum that is relevant to the development of the Arabic language teaching process for Indonesian Beginner Student, it can be concluded that the curriculum recommended by researchers is the curriculum in teaching Arabic for Indonesian Beginner students by using Homonyms in KBBI Dictionary from letters A to letters Z. Through this curriculum, students find it easier to learn Arabic because researches try to decipher word words in terms of the meaning of the two languages ​​in the learning module. This study aimed to propose a curriculum in teaching Arabic for Indonesian Beginner Students by using Homonyms Indonesian KBBI Dictionary from letters A to letters Z.